Persepsi Aparatur Sipil Negara IAIN Ponorogo terhadap Mekanisme Pemotongan Gaji untuk Zakat Penghasilan - Azam, Shelna Azima; Rokamah, Ridho (Nidhomiya: Research Journal of Islamic Philanthropy and Disaster, 2022)
ASN's perception of the mechanism of salary deductions at IAIN Ponorogo affects the payment of income zakat paid by each ASN. Although different needs regarding both personal and institutional programs, salary deductions are also in accordance with state orders and in accordance with the law stipulated in Subsection 58 paragraph (1) of PP 36/2021 which states that it is possible to deduct workers' wages, provided that the total amount of wage deductions is a maximum of 50% of every payment of wages received by workers (subsection 65 PP 36/2021). This is in accordance with the State Constitution and has been through the agreement of both parties between the party to be cut and the salary cut. The purpose of this study was to identify how the perception of ASN IAIN Ponorogo regarding salary deductions for income zakat which started from the L-Ziswaf program of IAIN Ponorogo. This research method uses a descriptive qualitative approach, primary and secondary data sources with a total of 8 ASN informants and 2 L-Ziswaf treasurers and the central treasurer of IAIN Ponorogo. Data analysis based on interviews, documentation, and salary slips of one ASN IAIN Ponorogo. The result of the study is obtaining various ASN perceptions regarding the salary deduction system for income zakat at IAIN Ponorogo. Through the perception of ASN, it can be concluded that the perception affects participation in the payment of income zakat in IAIN Ponorogo with the salary deduction method. However, not all of them participate in salary deductions for income zakat, but there are those who follow for infaq, alms, cooperatives, and mini bank. Persepsi ASN mengenai mekanisme potong gaji IAIN Ponorogo mempengaruhi pembayaran zakat penghasilan yang ditunaikan oleh ASN masing-masing. Walaupun berbeda-beda kebutuhan baik perihal pribadi maupun program institusi, pemotongan gaji juga sesuai dengan perintah negara dan sesuai dengan undang-undang yang ditetapkan pada Pasal 58 ayat (1) PP 36/2021 yang menyebut dimungkinkan dilakukannya pemotongan upah pekerja dengan ketentuan jumlah keseluruhan pemotongan upah paling banyak adalah 50% dari setiap pembayaran upah yang diterima pekerja (Pasal 65 PP 36/2021). Hal ini sudah sesuai dengan Undang-Undang Dasar negara dan sudah melalui persetujuan kedua belah pihak antara pihak yang akan dipotong dan yang memotong gaji. Tujuan penelitian ini adalah untuk menganalisis bagaimana persepsi ASN IAIN Ponorogo mengenai pemotongan gaji untuk zakat penghasilan yang bermula dari program L-Ziswaf IAIN Ponorogo. Metode penelitian ini menggunakan metode pendekatan kualitatif deskriptif, sumber data primer dan sekunder dengan jumlah informan sebanyak 8 orang ASN dan 2 bendahara L- Ziswaf dan bendahara pusat IAIN Ponorogo. Analisis data berdasarkan wawancara, dokumentasi, dan slip gaji salah satu ASN IAIN Ponorogo. Hasil penelitian, yaitu diperoleh berbagai persepsi ASN mengenai sistem potong gaji untuk zakat penghasilan di IAIN Ponorogo. Melalui persepsi ASN dapat disimpulkan bahwa persepsi mempengaruhi keikutsertaan dalam pembayaran zakat penghasilan di lingkungan IAIN Ponorogo dengan metode potong gaji. Tetapi, tidak semua mengikuti potong gaji untuk zakat penghasilan, melainkan ada yang mengikuti untuk infaq, sedekah, koperasi, dan mini bank.